Extreme resonance line profile variations in the ultraviolet spectra of NGC 1624-2: probing the giant magnetosphere of the most strongly magnetized known O-type star. Issue 2 (28th November 2018) - David-Uraz, A; Erba, C; Petit, V; Fullerton, A W; Martins, F; Walborn, N R; MacInnis, R; Barbá, R H; Cohen, D H; Maíz Apellániz, J; Nazé, Y; Owocki, S P; et al.
ABSTRACT: In this paper, we present high-resolution HST/COS observations of the extreme magnetic O star NGC 1624-2. These represent the first ultraviolet spectra of this archetypal object. We examine the variability of its wind-sensitive resonance lines, comparing it to that of other known magnetic O stars. In particular, the observed variations in the profiles of the C  iv and Si  iv doublets between low state and high state are the largest observed in any magnetic O-type star, consistent with the expected properties of NGC 1624-2's magnetosphere. We also observe a redshifted absorption component in the low state, a feature not seen in most stars. We present preliminary modelling efforts based on the Analytic Dynamical Magnetosphere (ADM) formalism, demonstrating the necessity of using non-spherically symmetric models to determine wind/magnetospheric properties of magnetic O stars.